What drives international stock return comovements? - Bohui Zhang (Asian Development Bank Institute (ADBI), 2020)
This paper presents new evidence on international financial market integration using stock analyst earnings forecasts from 37 countries. By examining cash flow and discount rate news co-movements, we find that the financial and economic aspects of global market integration have diverged over time as financial integration has developed particularly more rapidly than economic integration over the past decade. However, this divergence is less severe in emerging markets when compared with developed markets, where financial integration has proceeded at a slower pace. We find that financial integration has developed relatively slowly in emerging markets due to the hampering effects of their poor information environments.
Keywords: G15; F36; 330; financial market integration; stock analysts; cash flows; discount rates; R2